Engineering of the qubit initialization in an imperfect physical system. (5th August 2021) - Chen, Tianfeng; Wan, Lin; Qiu, Jiamin; Peng, Hong; Lu, Jie; Yan, Ying
Abstract: We propose a method to engineer the light matter interaction while initializing a qubit present of physical constraints utilizing the inverse engineering. Combining the multiple degrees of freedom in the pulse parameters with the perturbation theory, we develop pulses to initialize the qubit within a tightly packed frequency interval to an arbitrary superposition state with high fidelity. Importantly, the initialization induces low off-resonant excitations to the neighboring qubits, and it is robust against the spatial inhomogeneity in the laser intensity. We apply the method to the ensemble rare-earth ions system, and simulations show that the initialization is more robust against the variations in laser intensity than the previous pulses, and reduces the time that ions spend in the intermediate excited state by a factor of 17. The method is applicable to any systems addressed in frequency such as nitrogen-vacancy centers, superconducting qubits, quantum dots, and molecular qubit systems.